2022
DOI: 10.3390/jcm11226663
|View full text |Cite
|
Sign up to set email alerts
|

Orthobiologic Injections for the Treatment of Hip Osteoarthritis: A Systematic Review

Abstract: The use of orthobiologics is gaining increasing interest as a minimally invasive treatment for hip osteoarthritis (OA). The aim of this study was to investigate the evidence about the safety and efficacy of these products. A systematic review of the literature was performed according to the PRISMA and Cochrane guidelines. The study quality was assessed using the RoB 2.0 for randomized controlled trials (RCTs) and the modified Coleman Methodology Score (mCMS) for all studies. A total of 20 clinical studies (735… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 55 publications
0
1
0
Order By: Relevance
“…[14][15][16] However, most evidence on the clinical effectiveness of IA-HA comes from research on knee OA, 17,18, while the effects reported for the hip, shoulder, and ankle joints are limited. 17 The evidence suggests that IA-HA products with high MW; defined as greater than 3,000 kDa) have better effectiveness and safety for OA of the knee than lower MW products. 13,18,19 Why Is it Important to Do This Review?…”
Section: Context and Policy Issuesmentioning
confidence: 99%
“…[14][15][16] However, most evidence on the clinical effectiveness of IA-HA comes from research on knee OA, 17,18, while the effects reported for the hip, shoulder, and ankle joints are limited. 17 The evidence suggests that IA-HA products with high MW; defined as greater than 3,000 kDa) have better effectiveness and safety for OA of the knee than lower MW products. 13,18,19 Why Is it Important to Do This Review?…”
Section: Context and Policy Issuesmentioning
confidence: 99%
“…Newer orthobiologic therapies like Platelet-Rich Plasma (PRP) or stem cell hip injections are also becoming more commonly seen in treatment for hip OA. These injections aim to alleviate pain and improve joint function in individuals with hip OA by harnessing the regenerative properties of the injected substances [22]. Studies investigating hip injections, particularly PRP and cell-based therapies, have shown promising results in reducing hip pain and enhancing joint function [22].…”
Section: Current Treatment For Common Hip Conditionsmentioning
confidence: 99%
“…These injections aim to alleviate pain and improve joint function in individuals with hip OA by harnessing the regenerative properties of the injected substances [22]. Studies investigating hip injections, particularly PRP and cell-based therapies, have shown promising results in reducing hip pain and enhancing joint function [22]. However, the evidence is still evolving with limitations including heterogeneity in injected products and the need for further high-quality research to establish their efficacy and optimize treatment protocols [22].…”
Section: Current Treatment For Common Hip Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these challenges, treating damaged cartilages by MSC is promising, and further research in this area could lead to new and effective treatments for this debilitating condition. 8 , 40 , 41 …”
Section: Cellular Therapymentioning
confidence: 99%